Marriage Readiness for Late Adolescence in South Sulawesi - Eka Sufartianinsih Jafar; Dian Novita Siswanti; Novita Maulidya Jalal; Wilda Ansar (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2021)
This study aims to analyze indicators of marriage readiness for late adolescents in South Sulawesi. This study used a survey research design using a questionnaire. The research subjects were 860 adolescents aged 15-20 years who came from various levels of education, namely SMA (46.1%) SMK (4%) and undergraduate students (45.5%). The results showed that there are several indicators of marriage readiness in late adolescence. They are (1) economic stability by 51% (2) high education by 22.5%, (3) character adjustment with a partner by 35.6%, (4) parental consent by 26%. In terms of readiness for marriage, about 65.6% of adolescents stated they were not ready to marry, 23.6% were less ready to marry, 5.5% were quite ready, 5.1% were ready, and only 2.5% of them stated they were very ready to marry. In terms of the preparation needed to live a harmonious marriage, (1) communication skills by 59.9%, (2) skills in educating and caring for children 47.9%, (3) work 46.7%, and (4) emotional management 34.5%. While the things that concern adolescents from marriage are 67.5% infidelity, 60.9% being abused, dumped/ignored 45.3%, economically pressured 40.1%, and 29.8% not getting freedom. The implication of this study is to increase the knowledge of related parties, both parents, the community, and the government regarding the description of marriage readiness in late adolescence as material for providing premarital preparation/premarital education to adolescents so that late teens can prepare themselves to fulfill early adult development, namely choosing a partner and marry.